Can disease activity in patients with psoriatic arthritis be adequately assessed by a modified Disease Activity index for PSoriatic Arthritis (DAPSA) based on 28 joints?. Issue 12 (20th September 2018) - Michelsen, Brigitte; Sexton, Joseph; Smolen, Josef S; Aletaha, Daniel; Krogh, Niels Steen; van der Heijde, Désirée; Kvien, Tore K; Hetland, Merete Lund
Abstract : Objective: To test the psychometric performance of a modified Disease Activity index for PSoriatic Arthritis (DAPSA) using 28 instead of 66 swollen/68 tender joint counts (SJC/TJC). Methods: We included patients with psoriatic arthritis (PsA) from the Danish national quality registry DANBIO, divided into examination (n=3157 patients, 23987 visits) and validation cohorts (n=3154 patients, 24160 visits). We defined DAPSA28 = (28TJC × conversion factor1 ) + (28SJC × conversion factor2 ) + patient global (0–10VAS) + pain (0–10VAS) + C reactive protein (CRP) (mg/dL). Identification of the conversion factors was performed by generalised estimating equations in the examination cohort and evaluation of criterion, correlational and construct validity in the validation cohort. Results: We estimated DAPSA28 = (28TJC × 1.6) + (28SJC × 1.6) + patient global (0–10VAS) + pain (0–10VAS) + CRP (mg/dL). Criterion validity: DAPSA/DAPSA28 had comparable discriminative power expressed as standardised mean difference (DAPSA, 0.90; DAPSA28, 0.93) to distinguish between patients in high and low disease activity. Kappa with quadratic weighting of DAPSA/DAPSA28 disease activity states was high: 0.92 (95% CI 0.92 to 0.92). Standardised response means for DAPSA/DAPSA28 were –0.96/–0.92 for visits after biological DMARD-initiation. Correlational validity: Baseline DAPSA/DAPSA28 had high correlation with 28-joint disease activity score with CRP (r=0.87/r=0.93), simplified disease activity index (r=0.92/r=0.99), p<0.001. Bland-Altman plot showed better agreement between DAPSA/DAPSA28 for low than high disease activity. Construct validity: DAPSA/DAPSA28 were similarly correlated to Health Assessment Questionnaire; r=0.60/0.62, p<0.001. DAPSA/DAPSA28 discriminated patients reporting their symptom state as acceptable versus not acceptable equally well: mean (SD) 9.1 (8.7)/8.4 (8.0) and 24.2 (14.9)/22.5 (13.8), respectively. Conclusion: Our study suggests that data sets with only 28-joint counts available can be used to calculate DAPSA28, especially in patients with low disease activity. DAPSA28 showed good criterion, correlational and construct validity and sensitivity to change. Still, our results support that 66/68 joint count should be performed and the original DAPSA should be preferred in PsA.